Bezier curves interpolation with end point constraints on road map - Zakaria, Wan Zafira Ezza Wan; Ramli, Ahmad; Ali, Jamaludin Md (AIP conference proceedings, 2019)
This paper presents a path or curve generated based on Bezier curve. Derivation of smooth curve is one important subject for good visualization. Bezier curve is a smooth parametric curve but it is not a simple problem to properly assign its control points to determine the shape of the Bezier curve. Therefore, the Bezier curve of n-th order is derived with the end point constraints, which are location and velocity. Results and visualization comparisons between interpolation of Cubic and Quartic Bezier curve are shown and discussed in this paper. Application on reconstructing a curve from a road map is shown.